Disturbance Decoupling with Preview for Two-Dimensional Systems - Ntogramatzidis, Lorenzo; Michael, C.; Ran, Y. (Elsevier, 2008)
In this paper a solution is given to the exact disturbance decoupling problem (DDP) for two-dimensional (2-D) systems, whereby the control action consists of a static local state feedback and a preview function of the signal to be rejected. Importantly, stability of the closed loop is taken into account.